Knowledge and its utilization - Frimpong, Isaac (Univerzita Pardubice, 2025)
The thesis summarizes the basic views on the concept of knowledge, its types, and utilization. It presents an assessment of selected knowledge theories and their impact on competitiveness. Several use cases are defined and assessed in the context of criteria identified through the literature review. The most important findings are discussed and recommendations towards improvement of competitiveness are presented.
Keywords: znalost; využití; hodnocení; konkurenceschopnost; případ užití; kritéria; alternativy; knowledge; utilization; assessment; competitiveness; use case; criteria; alternatives